Two New Flavonoids and Biological Activity of Astragalus abyssinicus (Hochst.) Steud. ex A. Rich. Aerial Parts - El Dib, R. A.; Soliman, H. S. M.; Hussein, M. H.; Attia, H. G. (Drug Research, 2015)
2 new flavonoid glycosides, kaempferol 3-O-(4″,6″-di-O-α-L-rhamnopyranosyl)-β-D-glucopyranoside (1) and quercetin 3-O-(4″,6″-di-O-α-L-rhamnopyranosyl)-β-D-glucopyranoside (2), were isolated from the n-butanol soluble fraction of the methanol extract (BF) of Astragalus abyssinicus aerial parts, together with 3 known compounds, rutin (3), kaempferol 3-O-β-D-rutinoside (4) and 5,7,4′-trihydroxy-3′-methoxyisoflavone (5). The structures of the isolated compounds were characterized on the basis of UV, NMR and negative ESI-MS analyses. The BF fraction showed in vitro weak antibacterial activity against Staphylococcus aureus, while 2 and 3 exhibited in vitro antioxidant activity higher than ascorbic acid using DPPH free radical scavenging activity method.
Keywords: Astragalus abyssinicus; Fabaceae; Isolation; Flavonoids; Antibacterial activity; Antioxidant activity